1998
DOI: 10.1111/j.1574-6941.1998.tb00541.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonisation and transmission of lux-marked and wild-type Aeromonas salmonicida strains in Atlantic salmon (Salmo salar L.)

Abstract: Colonisation and transmission of Aeromonas salmonicida in Atlantic salmon was investigated using wild‐type and lux‐marked strains of A. salmonicida. An initial intra‐peritoneal (i.p.) challenge showed that lux‐marked cells were virulent only when injected at concentrations ≥109 cfu ml−1 and significantly less infective than wild‐type MT463. The low virulence of A. salmonicida MT463 luxAB was probably due to loss of the proteinaceous A‐layer, which is an important virulence factor involved in both intra‐ and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…(, ), Svendsen & Bøgwald (), Ferguson et al . () could not be confirmed. Still, given the relatively high threshold limit of luminescence detection, an attachment of a low number of bacteria to the skin cannot be ruled out.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…(, ), Svendsen & Bøgwald (), Ferguson et al . () could not be confirmed. Still, given the relatively high threshold limit of luminescence detection, an attachment of a low number of bacteria to the skin cannot be ruled out.…”
Section: Discussionmentioning
confidence: 86%
“…Bioluminescence imaging (BLI) has been applied for monitoring A. salmonicida in dead Atlantic salmon ( Salmo salar ) (Ferguson et al . ). However, requirement for an exogenous addition of aldehyde for BLI visualization and incorporation of luciferase genes into A. salmonicida significantly lowered the virulence of the bacterium (Ferguson et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The gastrointestinal tract, the gill epithelium and the skin have all been considered as entry points for pathogenic bacteria in fish (Inglis, Roberts & Bromage 1993; Grisez, Chair, Sorgeloos & Ollevier 1996; Olsson, Jöborn, Westerdahl, Blomberg, Kjelleberg & Conway 1996; Svendsen & Bøgwald 1997; Ferguson, Bricknell, Glover, Macgregor & Prosser 1998; O’Toole, Von Hofsten, Rosqvist, Olsson & Wolf‐Watz 2004). A. salmonicida has been isolated from the intestine of salmonids (Ringø & Olsen 1999; Lødemel, Mayhew, Myklebust, Olsen, Espelid & Ringø 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Aeromonads that are fish pathogens are easily transmitted horizontally by moribund fish that shed large quantities of bacteria into the water column and cross‐infect cohabitant fish (Ferguson et al. ). Studies on A. salmonicida showed that moribund or dead fish could shed up to 10 5 –10 8 CFU/fish per hour (Rose et al.…”
mentioning
confidence: 99%